Eating out of home and its correlates in 10 European countries. The European Prospective Investigation into Cancer and Nutrition (EPIC) study. - Orfanos, P; Naska, A; Trichopoulos, D; Slimani, N; Ferrari, P; van Bakel, M; Deharveng, G; Overvad, K; Tjønneland, A; Halkjaer, J; Santucci de Magistris, M; Tumino, R; et al. (2007)
OBJECTIVE: To compare the average out-of-home (OH) consumption of foods and beverages, as well as energy intake, among populations from 10 European countries and to describe the characteristics of substantial OH eaters, as defined for the purpose of the present study, in comparison to other individuals. DESIGN: Cross-sectional study. Dietary data were collected through single 24-hour dietary recalls, in which the place of consumption was recorded. For the present study, substantial OH eaters were defined as those who consumed more than 25% of total daily energy intake at locations other than the household premises. Mean dietary intakes and the proportion of substantial OH eaters are presented by food group and country. Logistic regression analyses were used to estimate the odds of being a substantial OH eater in comparison to not being one, using mutually adjusted possible non-dietary determinants. SETTING: Ten European countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC). SUBJECTS: The subjects were 34 270 individuals, 12 537 men and 21 733 women, aged 35-74 years. RESULTS: The fraction of energy intake during OH eating was generally higher in northern European countries than in the southern ones. Among the food and beverage groups, those selectively consumed outside the home were coffee/tea/waters and sweets and, to a lesser extent, cereals, meats, added lipids and vegetables. Substantial OH eating was positively associated with energy intake and inversely associated with age and physical activity. Substantial OH eating was less common among the less educated compared with the more educated, and more common during weekdays in central and north Europe and during the weekend in south Europe. CONCLUSIONS: Eating outside the home was associated with sedentary lifestyle and increased energy intake; it was more common among the young and concerned in particular coffee/tea/waters and sweets.